Peningkatkan Hasil Belajar Pendidikan Agama Islam Materi Asmaulhusna Menggunakan Metode Make A Match pada Siswa SDN 11 Bengkulu Selatan - Rikasti Rikasti (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
The purpose of this study was to determine the Improvement of Islamic Religious Education Learning Outcomes on Asmaulhusna Material for students using the Make A Match Method. The type of research that researchers use is class action research. This research was conducted in the 2023 school year. The data source I took was the main or primary data source, namely class IV students of SDN 11 Bengkulu Selatan consisting of 20 students. Supplementary or secondary data collection techniques I took from the teacher as an observation when the learning process took place for 3 cycles, namely cycle 1, cycle 2 and cycle 3. Data collection is done using written tests. From the results of the researchers, the Aqidah learning outcomes of students have increased by using Make a Match. This is evidenced by the percentage of learning outcomes in stage I 55%, stage II 75% and stage III 90%. It is from these results that researchers assume that learning outcomes have improved. The contribution of the results of this study as information in the field of Islamic religious education and as a novelty of findings on the use of the make a match method in learning asmaulhusna material in dadsar schools.